Collective Action in Indonesian Agricultural Marketing: What Do Farmers Gain? - Dyah Ayu Suryaningrum; Baiq Yulfia E. Yanuartati; Ni Made Wirastika Sari (LOCUS MEDIA PUBLISHING, 2026)
Smallholder farmers in Indonesia often face limited market access, weak bargaining power, high transaction costs, and reliance on middlemen. Collective action has been promoted as a strategy to address these constraints; nevertheless, the specific gains farmers receive from collective action in agricultural marketing remain dispersed across different studies. This article aims to review what Indonesian farmers gain from collective action in agricultural marketing. Using a narrative literature review, this study synthesizes Scopus-indexed publications on farmer groups, cooperatives, collective marketing, and related institutional arrangements in Indonesian agriculture. The findings show that collective action provides farmers with numerous advantages, including improved market access, stronger bargaining power, reduced dependence on middlemen, better knowledge sharing, and institutional strengthening. However, these gains are hindered by weak governance, limited managerial capacity, poor communication, elite domination, digital gaps, and insufficient institutional support. The review suggests that collective action should be strengthened not only as an organizational model, but also as a farmer-centered marketing strategy supported by good governance, digital access, direct market linkages, and inclusive participation.